NILAI PERSAHABATAN DALAM NOVEL ANAK SEMUA BANGSA KARYA PRAMOEDYA ANANTA TOER - Suyono, Suyono; Gafar, Abdoel; Supriyati, Supriyati (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
The Purpose of this study is to describe the value of friendship in the novel Anak Semua Bangsa karya Pramoedya Ananta Toer. This type of research is descriptive research. This descriptive research produces data in the form of qualitations. Descriptive research is a study that can solve data by describing. The data are words, sentences or dialogues and quotations contained in Pramoedya Ananta Toer’s Anak Semua Bangsa, focused on characters’ frienship values in the novel The data analysis activities in this study are carried out with following steps. Analyzing data based on aspects obtained in the word, sentence, or digging of dialogue related to friendship values, describing data, validating data by triangulating data, consulting data analysis to experts wich in this case guided by supervisors, matched with teory, and adapt to research methods and formulate conclusions